2019
DOI: 10.1073/pnas.1904311116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C2CD4A as a human diabetes susceptibility gene with a role in β cell insulin secretion

Abstract: Fine mapping and validation of genes causing β cell failure from susceptibility loci identified in type 2 diabetes genome-wide association studies (GWAS) poses a significant challenge. The VPS13C-C2CD4A-C2CD4B locus on chromosome 15 confers diabetes susceptibility in every ethnic group studied to date. However, the causative gene is unknown. FoxO1 is involved in the pathogenesis of β cell dysfunction, but its link to human diabetes GWAS has not been explored. Here we generated a genome-wide map of FoxO1 supere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 68 publications
(88 reference statements)
4
61
4
Order By: Relevance
“…These questions have been pursued using mouse and fish knockout models and relevant cell lines. In contrast to earlier findings (15), we observed that global C2cd4a deletion in the mouse exerted no effects on insulin secretion in vitro or in vivo. These findings are consistent with the considerably (10-fold) lower expression of C2cd4a than C2cd4b in mouse islets and derived β cell lines (Supp.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These questions have been pursued using mouse and fish knockout models and relevant cell lines. In contrast to earlier findings (15), we observed that global C2cd4a deletion in the mouse exerted no effects on insulin secretion in vitro or in vivo. These findings are consistent with the considerably (10-fold) lower expression of C2cd4a than C2cd4b in mouse islets and derived β cell lines (Supp.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 1) though we would emphasise that no attempt was made here to quantify protein (rather than mRNA) levels. The reasons for the differences between the present study and that of Kuo et al (15) with respect to C2cd4a are presently unclear, although this may reflect differences in the targeting strategies used to generate the different mouse mutants or genetic background and general housing conditions. Nonetheless, given that our work involved global inactivation of this gene we cannot exclude the possibility that compensatory changes occur in other tissues, or in islet cell other than β cells, that mitigate the effects of deleting C2cd4a in the β cell.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…An example of acquired transcriptional abnormalities leading to altered β-cell function is FoxO1, a nutrient-regulated transcription factor whose nutrient excess-driven failure leads first to metabolic inflexibility (Kim-Muller et al, 2014), and then to outright β-cell dedifferentiation (Cinti et al, 2016;Sun et al, 2019;Talchai et al, 2012). This is achieved in part by direct actions on glucose metabolism (Kuo et al, 2019b) and in part by regulating lineage stability (Kuo et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%